Effects of radio frequency exposure on hatching rate and development period of Ae. albopictus (skuse) (diptera: culicidae) - Nik Abdull Halim, Nik Muhammad Hanif; Mat Seleei, Nur Ma Aeina Shafiqah; Che Dom, Nazri; Dapari, Rahmat; Agyemang-Badu, Samuel Yaw (Univ. of Malaya, 2024)
Telecommunication technologies such as radio, cell phones, and television were developed to meet people's needs and have been widely used for decades. However, the invention relies on the transmission and reception of signals via radio (RF), which has increased concerns about the effects of RF fields on human health, including mosquito-borne diseases caused by exposure to these fields. To address these concerns, a study was conducted to evaluate the effects of exposure from RF on mosquitoes. The objective of this study is to determine the effects of exposure RF on hatching rate, development time, and egg morphology of the Aedes population. Under laboratory conditions, 50 Ae. albopictus eggs were exposed to three different exposures (control, low dose: 900 MHz and high dose: 18 GHz). The effects of exposure on hatching rate, development time and egg morphology were observed. This study revealed that higher doses of RF can shorten the hatching days of Aedes mosquitoes, but also slow down their development rate. In summary, this study provides important insights into the potential effects of exposure to RF on Aedes mosquito populations. Further research is needed to fully understand the effects of exposure RF on mosquito populations in natural environments and the potential public health implications.